English Online Learning in the Age of Global Pandemic: How Do Teachers and Students Feel? - Dwi Ilmiani; Muamaroh Muamaroh; Arif Nugroho (Center of Language and Cultural Studies, 2021)
Numerous researchers examine teachers' and students’ experiences in online learning at the college level. But there are a few sources that explore the implementation of English online classes at a Vocational high level. This issue is highly needed since the theory and researches dealing with this topic at this level still rare. The present study aims to close the gap by investigating the implementation of English online classes. The participants were six female English teachers and one hundred and seventy students at one state vocational high school in Central Java, Indonesia. The current research analyzes not only numerical data but also narrative data, which is customary for qualitative research to address the research questions. The instruments use questionnaires and a semi-structured interview. The overall results revealed that technology could help both teachers and students in conducting teaching and learning activities, even though some constraints such as limited data plan, network difficulties, and lack of teacher-students engagement. Furthermore, understanding materials became top rank challenged for participants during the online class. The current study contributes theoretical and practical benefits to improve the implementation of online learning in the age of global pandemics.